PENERAPAN MODEL PEMBELAJARAN KOOPERATIF KANCING GEMERINCING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI SMA NEGERI 11 PEKANBARU - Fopy Ariansi Ariansi; Maria Erna Erna; Betty Holiwarni Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The research about application of cooperative learning model of jingling studs has been done to know the improvement student’s achievement on the topic of reaction rate at class XI of SMA Negeri 11 Pekanbaru in November 2013. This kind of research is experiment research with randomized control group pretest-posttest design.The sample consisted of two classes, XI IPA 4 class as control class and X1 IPA 3 class as experiment class that randomly selected after testing normality and homogeneity test. Experimental classis a class that was treated by cooperative learning model of jingling studs, while the control class is a class that is not was treated by cooperative learning model of jingling studs. Analysis of data usedt-test technique. Results of data processing obtained tcount>ttable is 3,24>1,67 with an increase in the use of cooperative learning model of jingling studs to student achievement is 15,6%, it means that the application of cooperative learning model of jingling studs can improve student’s achievement on the topic of reaction rate at class XI of SMA Negeri 11 Pekanbaru.Keyword : Cooperative Learning, jingling studs, reaction rate*Mahasiswa